NRF2-GPX4/SOD2 axis imparts resistance to EGFR-tyrosine kinase inhibitors in non-small-cell lung cancer cells - Ma Chun-shuang; Lv Qian-ming; Zhang Ke-ren; Tang Ya-bin; Zhang Yu-fei; Shen Ying; Lei Hui-min; Zhu Liang (Acta Pharmacologica Sinica, 2021)
Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) have achieved satisfactory clinical effects in the therapy of non-small cell lung cancer (NSCLC), but acquired resistance limits their clinical application. NRF2 has been shown to enhance the resistance to apoptosis induced by radiotherapy and some chemotherapy. In this study, we investigated the role of NRF2 in resistance to EGFR-TKIs. We showed that NRF2 protein levels were markedly increased in a panel of EGFR-TKI-resistant NSCLC cell lines due to slow degradation of NRF2 protein. NRF2 knockdown overcame the resistance to EGFR-TKIs in HCC827ER and HCC827GR cells. Furthermore, we demonstrated that NRF2 imparted EGFR-TKIs resistance in HCC827 cells via upregulation of GPX4 and SOD2, and suppression of GPX4 and SOD2 reversed resistance to EGFR-TKIs. Thus, we conclude that targeting NRF2-GPX4/SOD2 pathway is a potential strategy for overcoming resistance to EGFR-TKIs.